2014
DOI: 10.4321/s0004-05922014000100014
|View full text |Cite
|
Sign up to set email alerts
|

Estudio de microsatélites en las abejas sin aguijón Melipona colimana y M. beecheii de Mesoamérica

Abstract: RESUMENEn este estudio, se ha analizado por primera vez la variabilidad de los loci de microsatélites en la especie silvestre de abejas sin aguijón Melipona colimana. Los datos obtenidos se han comparado con los de una población insular de la especie domesticada M. beecheii. Los resultados del genotipado de los individuos de M. colimana, indican que la secuencia de los loci de microsatélites está conservada dentro del género Melipona. Los parámetros poblacionales estudiados (número de alelos y valores de heter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
1
0
0
1
Order By: Relevance
“…Therefore it is highly likely that the degree of patchiness and the actual quality of the patches in the study sites are not affecting bee populations at detectable levels. Hurtado-Burillo et al (2014) compared the genetic richness of two Melipona species occurring in Mexico, M. colimana and M. beecheii, and found no significant differences in expected heterozygosity; moreover, these authors found no significant differences between the populations from deforested and conserved areas, with results similar to ours. However, as mentioned lines above, many lines of research arise to develop a more detailed view of the situation of stingless bees populations in this part of Mexico, but our results give the baseline for these studies.…”
Section: Discussionsupporting
confidence: 76%
“…Therefore it is highly likely that the degree of patchiness and the actual quality of the patches in the study sites are not affecting bee populations at detectable levels. Hurtado-Burillo et al (2014) compared the genetic richness of two Melipona species occurring in Mexico, M. colimana and M. beecheii, and found no significant differences in expected heterozygosity; moreover, these authors found no significant differences between the populations from deforested and conserved areas, with results similar to ours. However, as mentioned lines above, many lines of research arise to develop a more detailed view of the situation of stingless bees populations in this part of Mexico, but our results give the baseline for these studies.…”
Section: Discussionsupporting
confidence: 76%
“…Sobre este tema, los estudios realizados en México han sido principalmente sobre algunas especies de abejas de los géneros Scaptotrigona Moure, 1942(Quezada-Euán et al, 2012Hurtado-Burillo et al, 2013;2017), Melipona Illiger, 1806(May-Itzá et al, 2012Hurtado-Burillo et al, 2014), Trigona Jurine, 1807(Solórzano-Gordillo et al, 2015 y Plebeia Schwarz, 1938 (Francisco et al, 2011). De manera general, estos trabajos muestran que existe mucha variación y estructura genética entre regiones para una misma especie, sugiriendo que podrían existir más especies de las actualmente descritas (Quezada-Euán et al, 2012;Hurtado-Burillo et al, 2017).…”
Section: Las Abejas Sin Aguijón En Méxicounclassified